ANALISIS RANTAI PASOK METODE SUPPLY CHAIN OPERATION REFERENCE (SCOR) 12.0 PADA ATRIBUT RESPONSIVENESS DI PLAN F2 PT. M - Aurelia, Natasia; Ahmad; Salomon, Lithrone Laricha (Universitas Tarumanagara, 2025)
PT. M is one of the largest flat glass manufacturers in Indonesia, serving both domestic and export markets. In meeting demand, the company faces various challenges in managing its supply chain to become more efficient and responsive. In January 2025, a delay occurred in the production of export glass, extending from the initial target of 6 days to 9 days. To address this, the implementation of the SCOR 12.0 model was proposed as a solution for continuous improvement analysis. The focus of the analysis is on the responsiveness attribute, specifically RS.1.1 Order Fulfillment Cycle Time, with a Level 2 matrix of RS.2.2 Make Cycle Time. At Level 3, the largest time gaps were identified in RS.3.101 Produce and Test Cycle Time with a gap of 259 minutes, and RS.3.128 Stage Finished Product Cycle Time with a gap of 1040 minutes. The problem was found to stem from several internal factors causing the production PT. M is one of the largest flat glass manufacturers in Indonesia, serving both domestic and export markets. In meeting demand, the company faces various challenges in managing its supply chain to become more efficient and responsive. In January 2025, a delay occurred in the production of export glass, extending from the initial target of 6 days to 9 days. To address this, the implementation of the SCOR 12.0 model was proposed as a solution for continuous improvement analysis. The focus of the analysis is on the responsiveness attribute, specifically RS.1.1 Order Fulfillment Cycle Time, with a Level 2 matrix of RS.2.2 Make Cycle Time. At Level 3, the largest time gaps were identified in RS.3.101 Produce and Test Cycle Time with a gap of 259 minutes, and RS.3.128 Stage Finished Product Cycle Time with a gap of 1040 minutes. The problem was found to stem from several internal factors causing the production process to fail in meeting the desired quality standards, leading to a higher risk of glass loss and a need for stringent quality control measures. Based on these issues, two best practice proposals were recommended as key priorities to improve supply chain efficiency: BP.024 Supply Chain Optimization (SCO) and BP.165 Convergence of SCOR with Lean and Six Sigma. Process to fail in meeting the desired quality standards, leading to a higher risk of glass loss and a need for stringent quality control measures. Based on these issues, two best practice proposals were recommended as key priorities to improve supply chain efficiency: BP.024 Supply Chain Optimization (SCO) and BP.165 Convergence of SCOR with Lean and Six Sigma.